A new family of freshwater ascomycetes from Australia: Rivulataceae fam. nov., Rivulatus australiensis gen. et. sp. nov. (Diaporthomycetidae) - Fryar, Sally C.; Catcheside, David E.a. (Phytotaxa, 2025)
While surveying freshwater fungi on submerged wood in Australian rivers, lakes and streams, a new ascomycete species was collected and described. Maximum likelihood and Bayesian analyses indicate that Rivulatus australiensis is a new species, representing a new genus, Rivulatus and a new family, Rivulataceae, family incertae sedis, within the subclass Diaporthomycetidae. Although morphologically similar to Atractosporaceae, Rivulatus australiensis can be distinguished from this family by the black, carbonaceous ascomata and the shape of the ascus apical apparatus. Descriptions and illustrations of the new taxa are provided, along with comparisons with closely related taxa.